An investigation into menstruation and the right to education: the specific challenges puberty presents for adolescents girls - Keartland, Tarquin (My University, 2021)
The relationship between the onset of menses and young women’s experience of education has, in recent years, been at the forefront of addressing what has become known as ‘period poverty’. The specific challenges created by menstruation, particularly those created by a lack of access to menstrual products, are discussed with the intention of motivating for free products within the school environment. This is done from a constitutional rights-based perspective. The right to education, to equality, to dignity, and the principle of the best interest of the child are considered. In addition, the Human Capital Theory and Capabilities Theory are used to understand the immense benefits of education. As menstruation primarily affects women and girls, the importance of educating this demographic is explored and the consequences of under educating them investigated. The Sanitary Dignity Framework, which was published by the Department of Women, Youth, and Persons with Disabilities in 2019, is evaluated and shown to be a step in the right direction as far as addressing the puberty related issues faced by South African women and girls. Although primarily heuristic, this research did initially contemplate a small pilot study which intended to look at both the quantitative and qualitative experiences of girls at three schools in Gauteng. Sadly, the global COVID19 pandemic made this unfeasible, but the questionnaire and interview schedule developed for this purpose are included as they could potentially shape future research
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree Master of Laws (LLM)